Рассказы о животных: 1-4-е классы / [художник И. Есаулов] - Есаулов И. (Школьная библиотека, 2016)
Экземпляры: аб. ДБ (2017.29.09) / Инвентарный номер: 3473 / Цена: / Сис.шифр: 84(2Рос=Рус) / Авт.знак: Р 24 / ББК: 84(2Рос=Рус)